Pathophysiology of Sjögren's Syndrome and its diagnostic difficulty (Research, Society and Development, 2021)
Sjögren's Syndrome is an autoimmune disease, characterized by lymphocytic infiltration in the glandular epithelium, where it affects mainly the exocrine salivary and lacrimal glands. The study shows the classifications of the syndrome and the relation of autoantibodies related to its diagnosis. An integrative literature review was conducted, using articles published between the years 2010 and 2020, in Portuguese, English and Spanish languages that were published integrally in PubMed, SciELO and LILACS databases. Sicca syndrome is caused by genetic, environmental and hormonal factors. It affects mainly women with an average age of 56 years, where they have been suffering from hormonal imbalance. The autoimmune reaction is caused by the overstimulation of T cells and B cells that will stimulate hypergammaglobulinemia and the production of autoantibodies. In the long term the changes may mutate and lead to the development of non-Hodgkin lymphoma. The literature shows that the delay in diagnosis for Sjögren's Syndrome is due to the subtle symptoms that often go unnoticed or are confused with other pathologies. Anti-Ro and anti-La are the most frequent autoantibodies in patients with SS.